High-strength alkaline solution resistant long afterglow fluorescent powder and preparation method thereof

Through the composite envelope technology of phosphate and ethyl orthosilicate, a silicon phosphate oxide film is formed, which solves the problems of agglomeration and light decay of long afterglow phosphors in a strong alkaline environment, and achieves efficient luminescence and long-term stability in pH=13 environment.

CN119859524AActive Publication Date: 2025-04-22GUANGZHOU ZHUJIANG PHOTOELECTRIC NEW MATERIALS
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510073733.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-22
Estimated Expiration
2045-01-17

AI Technical Summary

Technical Problem

The existing long afterglow phosphor is difficult to maintain stability in a strong alkaline environment, and is prone to agglomeration and light decay problems, which cannot meet the application needs of alkaline liquids around pH=13.

Method used

The method of phosphate envelope and orthosilicate composite envelope is adopted to form a dense silicon phosphorus oxide film to enhance the alkali resistance of the phosphor.

Benefits of technology

In a strong alkaline solution with pH=13, the fluorescent powder has good fluidity, with a relative brightness of 82.0%-87.1%, and the afterglow maintenance rate of 60 minutes is less than 5%, which significantly improves the service life in a strong alkaline environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119859524A_ABST
    Figure CN119859524A_ABST
Patent Text Reader

Abstract

According to the long-afterglow fluorescent powder resistant to the high-strength alkaline solution, the preparation method of the long-afterglow fluorescent powder resistant to the high-strength alkaline solution and aluminate long-afterglow fluorescent powder, after being coated with phosphate, the aluminate long-afterglow fluorescent powder continues to be coated with tetraethoxysilane, and the long-afterglow fluorescent powder resistant to the high-strength alkaline solution is obtained. Phosphate is adopted for coating, after the phosphate is tightly attached to the fluorescent powder, silicon oxide is continuously used for composite coating, compactness of a formed silicon phosphorus oxide film is achieved, and erosion can be effectively resisted in a strong alkaline solution environment; the problems of agglomeration and luminous decay of aluminate long-afterglow fluorescent powder are solved, and the service life of the aluminate long-afterglow fluorescent powder in a strong alkaline solution is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of luminescent powders, and in particular relates to a long afterglow phosphor resistant to high-strength alkaline solutions and a preparation method thereof. Background Art

[0002] Long afterglow phosphors are materials that continue to emit light for minutes, hours or even days after the excitation stops. Due to their special optical phenomena, many long afterglow phosphors have been successfully used in emergency lighting, in vivo biological imaging, and optical information storage. The most widely used long afterglow phosphor SrAl2O4:Eu 2+ ,Dy 3+ It is a phosphor with bright green long afterglow (λem=510nm) first discovered by Matsuzawa et al. in 1996. 2+ 、Ce 3+ or Mn 2+ As the luminescence center, Dy 3+ 、Nd 3+ Many other aluminate, silicate, and nitride-based long-lasting phosphors doped with rare earth ions as carrier capture centers have been gradually developed, such as Sr4Al 14 O 25 :Eu 2+ ,Dy 3+ ,β-Zn3(PO4)2:Mn 2+ 、M2Si5N8:Eu 2+ ,Tm 3+ (M=Ca, Ba), etc. The current research on long afterglow phosphors mainly focuses on the luminescent center, matrix carrier, luminescent brightness, and afterglow duration. There are few studies on long afterglow phosphors in specific application scenarios, such as sunlight exposure environment, humid environment, strong acid environment, strong alkaline environment, etc. For example, the application of long afterglow phosphors in textiles and printing is largely restricted by the shortcoming of poor alkali resistance.

[0003] In the prior art, there are no reports on the research of alkali resistance of long afterglow phosphors. Currently, only the research on improving alkali resistance of other systems can be used as a reference. For example, patent document CN106700662A discloses a method for preparing acid-alkali-resistant and anti-corrosion aluminum pigments. In an alcohol system, long-chain silane coupling agents and silicates are used as precursors. The two synergistically coat the modified aluminum pigments. After washing and drying, Al / SiO2 composite pigments with high acid and alkali resistance and high corrosion resistance can be obtained. The best sample can be stable for 48 hours in 0.1mol / L hydrochloric acid solution and sodium hydroxide solution with pH=12. However, this degree of alkali resistance cannot meet the needs of the application end for long afterglow phosphors that generally need to be immersed in alkaline solution with pH=13.

[0004] Patent document CN114574191B discloses a method for obtaining acid-resistant and alkali-resistant blue phosphor by coating 5-sulfosalicylic acid with barium sulfate, which comprises the following steps: fully dissolving the raw material 5-sulfosalicylic acid in water; adding sodium hydroxide solution to the 5-sulfosalicylic acid solution, then adding sodium sulfate solution, slowly dripping barium chloride solution to obtain a white precipitate; using a high-speed centrifuge to centrifuge and wash the white precipitate with deionized water; drying the white precipitate and sieving it to obtain the acid-resistant and alkali-resistant blue phosphor coated with 5-sulfosalicylic acid with barium sulfate. The method is simple, low-cost, and harmless to the environment. It is applied to agricultural production to convert ultraviolet rays in sunlight into blue light, further improving the efficiency of crop photosynthesis. And the coated phosphor obtained by this method is aimed at the application environment of strong alkaline pH=11 commonly used for pesticides, and the BaSO4 coating method can be realized.

[0005] However, in the solution environment of textile pigments and printing coatings, which generally have a pH of 13, Ba-based 2+ With SO4 2- The BaSO4 coating of the precipitation reaction is difficult to form a dense film on the surface of the phosphor. Therefore, the coated phosphor obtained by this method still cannot overcome the serious problems of agglomeration and light decay in this environment. Therefore, how to achieve the alkali-resistant coating technology of aluminate long-lasting phosphor to obtain a strong alkaline-resistant long-lasting phosphor is still a problem that needs to be solved. Summary of the invention

[0006] The present application provides a high-alkaline solution-resistant long-lasting phosphor and a preparation method thereof to solve the problems existing in the related art. The technical solution is as follows:

[0007] In a first aspect, the present invention provides a method for preparing a long-lasting phosphor resistant to high-strength alkaline solution, wherein the phosphor is an aluminate long-lasting phosphor, and its chemical formula is Sr x Al2O4:Eu 2+ ,Dy 3+ , where 0.6≤x≤1.2;

[0008] After the phosphor is coated with phosphate, it is further coated with ethyl orthosilicate to obtain the high-alkaline solution resistant long afterglow phosphor. x Al2O4:Eu 2+ ,Dy 3+ , the change of x value will affect its luminous color, but has no obvious effect on the alkali resistance of the phosphor. When the x value is 0.6-0.8, it emits blue-green light, when it is 0.8-0.9, it emits green light, and when it is 0.9-1.2, it emits yellow-green light.

[0009] In one embodiment, the phosphor is firstly ground before being phosphate coated:

[0010] Ball mill for 0.5 to 1 h according to the mass ratio of powder: water: grinding ball: 1: (1.2 to 1.7): (2.0 to 2.5), and sieve to obtain phosphor slurry.

[0011] In one embodiment, the process of phosphate coating of phosphor is as follows:

[0012] Add phosphate to the phosphor slurry, adjust the pH to 2-3, and stir at 125-155 rpm for 4-6 hours.

[0013] In one embodiment, the phosphate is a soluble phosphate; preferably, the phosphate is disodium hydrogen phosphate and / or sodium dihydrogen phosphate.

[0014] In one embodiment, the mass of the added phosphate is 10-16% of the mass of the phosphor.

[0015] In one embodiment, the process of using tetraethyl orthosilicate coating is:

[0016] After the phosphate coating is completed, ethyl orthosilicate is added, and ammonia water is used to adjust the pH to 8.5-10. After the temperature reaction is completed, the reaction is cooled to room temperature to obtain a phosphor slurry coated with silicon-phosphorus oxide.

[0017] In one embodiment, after adding tetraethyl orthosilicate, stirring is performed for 1-2 hours, and then ammonia water is used to adjust the pH to 8.5-10.

[0018] In one embodiment, the temperature-raising reaction conditions are: raising the temperature to 70-85° C. and stirring at 180-220 rpm for 2-3 hours.

[0019] In one embodiment, after coating with tetraethyl orthosilicate, the phosphor powder coated with silicon phosphorus oxide is obtained through separation, washing and drying; that is, the phosphor powder with long afterglow resistant to high-strength alkaline solution.

[0020] In a second aspect, an embodiment of the present application provides a long afterglow phosphor resistant to high-strength alkaline solutions, which is prepared by any of the above-mentioned methods for preparing a long afterglow phosphor resistant to high-strength alkaline solutions.

[0021] In one embodiment, the phosphor has good fluidity after being in a strong alkaline solution of pH=13 for one week.

[0022] In one embodiment, the relative brightness of the phosphor is 82.0%-87.1% after being exposed to a strong alkaline solution with a pH of 13 for one week.

[0023] In one embodiment, the phosphor has a 60-min afterglow maintenance rate change of less than 5% after being exposed to a pH=13 strong alkaline solution for one week.

[0024] The advantages or beneficial effects of the above technical solution include at least:

[0025] The present invention discloses a method for preparing a long afterglow phosphor resistant to high-strength alkaline solution, which first uses phosphate for coating, and after the phosphate and the phosphor are tightly bonded, silicon oxide is used for composite coating to form the compactness of the silicon-phosphorus oxide film. Through the sequential composite coating, the coating layer is tightly bonded inside and dense outside, which can effectively resist corrosion in a strong alkaline solution environment; solve the agglomeration and light decay problems of aluminate long afterglow phosphors, and increase the service life in a strong alkaline solution.

[0026] The invention discloses a high-alkaline solution-resistant long-afterglow phosphor, which can be used in a strong alkaline solution. After one week in a pH=13 strong alkaline solution, the phosphor has good fluidity, a relative brightness of 82.0%-87.1%, and a 60-minute afterglow maintenance rate change of less than 5%. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a SEM image of the phosphor coated with silicon-phosphorus oxide prepared in Example 3;

[0028] Figure 2 This is a graph showing the results of repeated parallel tests on the alkali resistance of the phosphors of Example 3 and Comparative Example 4. DETAILED DESCRIPTION

[0029] Hereinafter, only some exemplary embodiments are briefly described. As those skilled in the art will appreciate, the described embodiments may be modified in various ways without departing from the spirit or scope of the present application. Therefore, the following description is considered to be exemplary and non-restrictive in nature.

[0030] The main luminescent component of phosphor is metal ions. Under acidic and alkaline conditions, phosphor is particularly prone to agglomeration, which affects the fluidity of the product and makes the product unusable.

[0031] Therefore, the present invention provides a method for preparing a long-lasting phosphor resistant to high-strength alkaline solution, wherein the phosphor is an aluminate long-lasting phosphor, and its chemical formula is Sr x Al2O4:Eu 2+ ,Dy 3+ , where 0.6≤x≤1.2;

[0032] After the phosphor is coated with phosphate, it is further coated with ethyl orthosilicate to obtain the high-strength alkaline solution-resistant long-afterglow phosphor.

[0033] Because the film-forming reaction of phosphate on the surface of phosphor is slower than the hydrolysis film-forming reaction of ethyl orthosilicate on the surface of phosphor; therefore, phosphate coating is first performed, and then ethyl orthosilicate coating is used to ensure that as many -Si-OP- structural networks as possible are generated on the surface of phosphor particles. The composite coating of phosphate and silicon oxide is used, and the close adhesion of phosphate film and phosphor and the compactness of silicon phosphor oxide film are comprehensively utilized to solve the agglomeration and light decay problems of aluminate long afterglow phosphor.

[0034] In one embodiment, the phosphor is firstly ground before being phosphate coated:

[0035] Ball mill for 0.5 to 1 h according to the mass ratio of powder: water: grinding ball: 1: (1.2 to 1.7): (2.0 to 2.5), and sieve to obtain phosphor slurry.

[0036] After ball milling, the surface energy of the phosphor increases and the surface activity is enhanced, which is conducive to the subsequent precipitation of S on the surface of the phosphate and phosphor particles. r2+ 、Al 3+ The phosphate film is formed by the reaction, which is tightly attached to the surface. Therefore, the ball milling process before coating can not only formulate the corresponding particle size according to customer needs, but also improve the surface activity of the phosphor and enhance the reaction rate and bonding strength of the subsequent coating.

[0037] In one embodiment, the sieving can be performed by selecting a suitable sieve, and the sieve can be selected specifically according to the product requirements. Preferably, the sieving is performed by filtering with a 20-60 mesh sieve to obtain a phosphor with a corresponding particle size range.

[0038] In one embodiment, the process of phosphate coating of phosphor is as follows:

[0039] Add phosphate to the phosphor slurry, adjust the pH to 2-3, and stir at 125-155 rpm for 4-6 hours.

[0040] In one embodiment, hydrochloric acid is used to adjust the pH to 2-3.

[0041] In the process, hydrochloric acid is used to adjust the pH to acidic, which increases the film-forming rate of the phosphate film precipitation reaction and the degree of adhesion between the film and the surface of the phosphor particles; the lower the pH, the faster the reaction rate, but if the pH is too low, the phosphor will obviously decompose, resulting in a decrease in yield and luminescence brightness. In order to take into account both the reaction speed and the luminescence performance of the phosphor, the pH is set at 2-3.

[0042] In one embodiment, the phosphate is a soluble phosphate; preferably, the phosphate is disodium hydrogen phosphate and / or sodium dihydrogen phosphate.

[0043] In one embodiment, the mass of the added phosphate is 10-16% of the mass of the phosphor.

[0044] In one embodiment, the process of using tetraethyl orthosilicate coating is:

[0045] After the phosphate coating is completed, ethyl orthosilicate is added, and ammonia water is used to adjust the pH to 8.5-10. After the temperature reaction is completed, the reaction is cooled to room temperature to obtain a phosphor slurry coated with silicon-phosphorus oxide.

[0046] In one embodiment, after adding ethyl orthosilicate, the mixture is stirred for 1-2 hours, and then the pH is adjusted to 8.5-10 using aqueous ammonia. The tolerance of pure phosphate membrane to strong alkali is very poor, because there are a lot of H + In a strong alkaline solution, H + Rapid detachment destroys the integrity of the phosphate film and the bonding strength with the phosphor surface. Therefore, adding tetraethyl orthosilicate to form a composite film network with phosphate is a critical step. The alkaline tetraethyl orthosilicate can react with the H in the phosphate film. + The slow reaction converts the H in the phosphate membrane + Therefore, after adding ethyl orthosilicate, stir for 1-2 hours to remove a large amount of H in the phosphate membrane. + .

[0047] Ammonia is a weak base. The pH is adjusted to 8.5-10 with ammonia in order to hydrolyze ethyl orthosilicate and combine with phosphate to form a dense silicon-phosphorus oxide film. It is difficult for ethyl orthosilicate to hydrolyze silicon oxide under acidic conditions. Only under alkaline conditions can ethyl orthosilicate have a significant hydrolysis reaction. If the pH is lower than 8, the film-forming reaction speed is too slow. If the pH reaches 11, the silicon oxide will settle too quickly and the film will be uneven. In addition, if the pH is too high, the bonding strength between the phosphate film and the phosphor surface will be destroyed, resulting in a decrease in the product's alkali resistance.

[0048] In one embodiment, the temperature-raising reaction conditions are: raising the temperature to 70-85° C. and stirring at 180-220 rpm for 2-3 hours.

[0049] Sodium dihydrogen phosphate or disodium hydrogen phosphate slowly reacts with strontium aluminate long afterglow phosphor under acidic conditions to generate strontium dihydrogen phosphate and aluminum dihydrogen phosphate film coated on the surface of the phosphor particles; after adding ethyl acetate, the pH is adjusted to alkaline with ammonia water, and the ethyl acetate is hydrolyzed, so that strontium dihydrogen phosphate and H in the aluminum dihydrogen phosphate film are reacted. + Gradually separated, on the other hand, silicon oxide compounds and Al 3+ , Sr 2+ , P 5+The phosphor is coated with a dense [O-Sr-O-Si-OPO-Al]n network formed through oxygen bond connection, thereby improving the luminescence stability of the long afterglow phosphor in a strong alkaline solution without agglomeration.

[0050] Therefore, ethyl orthosilicate is alkaline in aqueous solution. First, ethyl orthosilicate is added to react for a period of time, and then the mildly reactive weak base ammonia water is used for alkaline adjustment. The hydrogen ions in the phosphate film can be slowly dragged out, thus avoiding the decrease in the bonding strength between the phosphate film and the phosphor. At the same time, the temperature of ethyl orthosilicate is increased to form a more dense phosphorus silicon oxide film structure network, thereby achieving the tightness of the film coating.

[0051] In one embodiment, after coating with tetraethyl orthosilicate, the phosphor powder coated with silicon phosphorus oxide is obtained through separation, washing and drying; that is, the phosphor powder with long afterglow resistant to high-strength alkaline solution.

[0052] In one embodiment, the separation is firstly performed by filtering through a 300-mesh screen, and then centrifugal dehydration is performed. After the coating is completed, filtering through a 300-mesh screen can remove large particles of phosphor powder that are agglomerated due to poor coating, which can not only make the particle size of the final product more uniform, but also further ensure the coating quality of the product.

[0053] In one embodiment, pure water is used for washing until the conductivity of the centrifuge liquid is ≤80 μS / cm.

[0054] In one embodiment, the drying is performed at 130-150° C. for 20-24 hours.

[0055] In a second aspect, an embodiment of the present application provides a long afterglow phosphor resistant to high-strength alkaline solutions, which is prepared by any of the above-mentioned methods for preparing a long afterglow phosphor resistant to high-strength alkaline solutions.

[0056] In one embodiment, the phosphor has good fluidity after being in a strong alkaline solution of pH=13 for one week.

[0057] In one embodiment, the relative brightness of the phosphor is 82.0%-87.1% after being exposed to a strong alkaline solution with a pH of 13 for one week.

[0058] In one embodiment, the phosphor has a 60-min afterglow maintenance rate change of less than 5% after being exposed to a pH=13 strong alkaline solution for one week.

[0059] The following is a further description with reference to specific embodiments.

[0060] Example 1

[0061] (1) The chemical formula is SrAl2O4:Eu 2+ ,Dy 3+The aluminate long afterglow phosphor powder was used as a raw material, and the powder: water: grinding ball mass ratio was 1:1.2:2.0, and the powder was ball-milled in a horizontal ball mill for 1 hour, and filtered through a 20-mesh screen to obtain a phosphor slurry;

[0062] (2) adding sodium dihydrogen phosphate (13% by weight of the phosphor) to the phosphor slurry, adjusting the pH to 2 with hydrochloric acid, and then stirring for 4 hours at a speed of 125 rpm to obtain a phosphate-coated phosphor slurry;

[0063] (3) adding ethyl orthosilicate having a phosphor mass concentration of 5% to the slurry obtained in step (2) while stirring, stirring for 1 hour, adding ammonia water to adjust the pH value to 9.0, increasing the stirring speed to 200 rpm, raising the temperature to 75° C., heating and stirring for 3 hours, stopping heating, cooling to room temperature, and filtering with a 300-mesh sieve to obtain a phosphor slurry coated with silicon-phosphorus oxide;

[0064] (4) The slurry of step (3) is centrifuged and dehydrated, and then washed again with pure water until the conductivity of the centrifugal liquid is ≤80 μS / cm, and then placed in an oven for drying at a temperature set to 135° C. for a drying time of 22 h to obtain a silicon-phosphorus oxide coated phosphor powder.

[0065] Example 2

[0066] (1) The chemical formula is SrAl2O4:Eu 2+ ,Dy 3+ The aluminate long afterglow phosphor powder was used as a raw material, and the powder: water: grinding ball mass ratio was 1: 1.7: 2.5, and the powder was ball-milled in a horizontal ball mill for 0.5 h, and filtered through a 40-mesh screen to obtain a phosphor slurry;

[0067] (2) adding 4% disodium hydrogen phosphate and 9% sodium dihydrogen phosphate by weight of the phosphor to the phosphor slurry, adjusting the pH to 3 with hydrochloric acid, and then stirring for 6 hours at a speed of 130 rpm to obtain a phosphate-coated phosphor slurry;

[0068] (3) adding ethyl orthosilicate having a phosphor mass concentration of 8% to the slurry obtained in step (2) while stirring, stirring for 1 hour, adding ammonia water to adjust the pH value to 9.0, increasing the stirring speed to 180 rpm, raising the temperature to 85° C., heating and stirring for 3 hours, stopping heating, cooling to room temperature, and filtering with a 300-mesh sieve to obtain a phosphor slurry coated with silicon-phosphorus oxide;

[0069] (4) The slurry of step (3) is centrifuged and dehydrated, and then washed again with pure water until the conductivity of the centrifugal liquid is ≤80 μS / cm, and then placed in an oven for drying at a temperature set to 150° C. for a drying time of 20 h to obtain a silicon-phosphorus oxide coated phosphor powder.

[0070] Example 3

[0071] (1) The chemical formula is SrAl2O4:Eu 2+ ,Dy 3+ The aluminate long afterglow phosphor powder was used as a raw material, and the powder: water: grinding ball mass ratio was 1: 1.5: 2.2, and the powder was ball-milled in a horizontal ball mill for 0.7 h, and filtered through a 60-mesh screen to obtain a phosphor slurry;

[0072] (2) adding sodium dihydrogen phosphate (13% by weight of the phosphor) to the phosphor slurry, adjusting the pH to 2 with hydrochloric acid, and then stirring for 4 hours at a speed of 130 rpm to obtain a phosphate-coated phosphor slurry;

[0073] (3) adding 10% ethyl orthosilicate by mass concentration of phosphor to the slurry obtained in step (2) while stirring, stirring for 2 h, adding ammonia water to adjust the pH value to 9.0, increasing the stirring speed to 220 rpm, raising the temperature to 70° C., heating and stirring for 3 h, stopping heating, cooling to room temperature, and filtering with a 300-mesh sieve to obtain a phosphor slurry coated with silicon-phosphorus oxide;

[0074] (4) The slurry of step (3) is centrifuged and dehydrated, and then washed again with pure water until the conductivity of the centrifugal liquid is ≤80 μS / cm, and then placed in an oven for drying at a temperature set to 135° C. for a drying time of 20 h to obtain a silicon-phosphorus oxide coated phosphor powder.

[0075] Example 4

[0076] (1) The chemical formula is SrAl2O4:Eu 2+ ,Dy 3+ The aluminate long afterglow phosphor powder was used as a raw material, and the powder: water: grinding ball mass ratio was 1: 1.5: 2.2, and the powder was ball-milled in a horizontal ball mill for 0.7 h, and filtered through a 60-mesh screen to obtain a phosphor slurry;

[0077] (2) adding sodium dihydrogen phosphate (10% by weight of the phosphor) to the phosphor slurry, adjusting the pH to 2 with hydrochloric acid, and then stirring for 4 hours at a speed of 125 rpm to obtain a phosphate-coated phosphor slurry;

[0078] (3) adding ethyl orthosilicate with a phosphor concentration of 8% by mass to the slurry obtained in step (2) while stirring, stirring for 1 hour, adding ammonia water to adjust the pH value to 8.5, increasing the stirring speed to 190 rpm, raising the temperature to 75° C., heating and stirring for 2 hours, stopping heating, cooling to room temperature, and filtering with a 300-mesh sieve to obtain a phosphor slurry coated with silicon-phosphorus oxide;

[0079] (4) The slurry of step (3) is centrifuged and dehydrated, and then washed again with pure water until the conductivity of the centrifugal liquid is ≤80 μS / cm, and then placed in an oven for drying at a temperature set to 145° C. for a drying time of 20 h to obtain a silicon-phosphorus oxide coated phosphor powder.

[0080] Example 5

[0081] (1) The chemical formula is SrAl2O4:Eu 2+ ,Dy 3+ Aluminate long afterglow phosphor powder was used as raw material, and ball-milled in a horizontal ball mill for 0.5 h at a powder: water: grinding ball mass ratio of 1:1.5:2.2, and filtered through a 40-mesh screen to obtain phosphor slurry;

[0082] (2) adding sodium dihydrogen phosphate (16% by weight of the phosphor) to the phosphor slurry, adjusting the pH to 2 with hydrochloric acid, and then stirring for 5 hours at a speed of 155 rpm to obtain a phosphate-coated phosphor slurry;

[0083] (3) adding ethyl orthosilicate having a phosphor mass concentration of 5% to the slurry obtained in step (2) while stirring, stirring for 2 h, adding ammonia water to adjust the pH value to 10.0, increasing the stirring speed to 180 rpm, raising the temperature to 70° C., heating and stirring for 2 h, stopping heating, cooling to room temperature, and filtering with a 300-mesh sieve to obtain a phosphor slurry coated with silicon-phosphorus oxide;

[0084] (4) The slurry of step (3) is centrifuged and dehydrated, and then washed again with pure water until the conductivity of the centrifugal liquid is ≤80 μS / cm, and then placed in an oven for drying at a temperature set to 150° C. for a drying time of 24 h to obtain a silicon-phosphorus oxide coated phosphor powder.

[0085] Comparative Example 1 (1) The chemical formula is SrAl2O4:Eu 2+ ,Dy 3+ The aluminate long afterglow phosphor powder was used as a raw material, and the powder: water: grinding ball mass ratio was 1: 1.5: 2.2, and the powder was ball-milled in a horizontal ball mill for 0.7 h, and filtered through a 60-mesh screen to obtain a phosphor slurry;

[0086] (2) adding sodium dihydrogen phosphate (23% by weight of the phosphor) to the phosphor slurry, adjusting the pH to 2 with hydrochloric acid, and then stirring for 4 hours at a speed of 130 rpm to obtain a phosphate-coated phosphor slurry;

[0087] (3) The slurry of step (2) is centrifuged and dehydrated, and then washed again with pure water until the conductivity of the centrifugal liquid is ≤80 μS / cm, and then placed in an oven for drying at a temperature set to 135° C. for a drying time of 20 h to obtain phosphorus oxide coated phosphor powder.

[0088] Comparative Example 2

[0089] (1) The chemical formula is SrAl2O4:Eu 2+ ,Dy 3+ The aluminate long afterglow phosphor powder was used as a raw material, and the powder: water: grinding ball mass ratio was 1: 1.5: 2.2, and the powder was ball-milled in a horizontal ball mill for 0.7 h, and filtered through a 60-mesh screen to obtain a phosphor slurry;

[0090] (2) Adding ethyl acetate with a phosphor mass concentration of 23% to the obtained slurry while stirring, stirring for 2 h, adding ammonia water to adjust the pH value to about 9.0, increasing the stirring speed to 220 rpm, raising the temperature to 70° C., heating and stirring for 3 h, stopping heating, cooling to room temperature, and filtering with a 300-mesh sieve to obtain a phosphor slurry coated with silicon-phosphorus oxide.

[0091] (3) The slurry of step (2) is centrifuged and dehydrated, and then washed again with pure water until the conductivity of the centrifugal liquid is ≤80 μS / cm, and then placed in an oven for drying at a temperature set to 135° C. for a drying time of 20 h to obtain a silicon oxide coated phosphor powder.

[0092] Comparative Example 3

[0093] This comparative example is basically the same as Example 3, except that the ball milling process in step (1) is deleted. The modified step (1) is: selecting a material with a chemical formula of SrAl2O4:Eu 2+ ,Dy 3+ Aluminate long afterglow phosphor is used as raw material, added in a powder: water mass ratio of 1:1.5 and stirred evenly, and filtered with a 60-mesh sieve to obtain phosphor slurry; the other steps are the same as those in Example 3.

[0094] Comparative Example 4

[0095] This comparative example is basically the same as Example 3, except that "filtering with a 300-mesh screen" is omitted in step (3). The modified step (3) is as follows: adding ethyl acetate with a phosphor mass concentration of 10% to the slurry obtained in step (2) while stirring, stirring for 2 hours, adding ammonia water to adjust the pH value to about 9.0, increasing the stirring speed to 220 rpm, raising the temperature to 70°C, heating and stirring for 3 hours, stopping heating, and cooling to room temperature to obtain a phosphor slurry coated with silicon-phosphorus oxide; the other steps are the same as those in Example 3.

[0096] Comparative Example 5

[0097] The difference between Comparative Example 5 and Example 3 is that in step (2), 13% of the mass of the phosphor by weight of sodium dihydrogen phosphate is added to the phosphor slurry, and then stirred for 12 hours with the rotation speed set to 130 rpm to obtain a phosphate-coated phosphor slurry. The other steps are the same as those in Example 3.

[0098] Comparative Example 6

[0099] The difference between Comparative Example 6 and Example 3 is that in step (3), 10% of the phosphor mass concentration of tetraethyl orthosilicate is added to the slurry obtained in step (2) while stirring, and the mixture is stirred for 2 h. Ammonia water is added to adjust the pH value to about 7.0, the stirring speed is increased to 220 rpm, the temperature is increased to 70°C, and the mixture is heated and stirred for 3 h. The heating is stopped, the mixture is cooled to room temperature, and the mixture is filtered through a 300-mesh sieve to obtain a phosphor slurry coated with silicon-phosphorus oxide. The other steps are the same as those in Example 3.

[0100] 1. The silicon-phosphorus oxide coated phosphor prepared in Example 3 was observed by electron scanning microscope. The SEM image is as follows: Figure 1 shown.

[0101] from Figure 1 It can be seen from the figure that the phosphor is a micron-sized sample with uniform particles.

[0102] 2. The phosphors of Examples 1-5 and Comparative Examples 1-4 were subjected to particle size analysis. The results are shown in Table 1.

[0103] Table 1 Particle size of phosphors of Examples 1-5 and Comparative Examples 1-4

[0104]

[0105] In Table 1, except for Comparative Example 4 with a particle size D50 of 26 μm, the particle sizes D50 of the other samples are basically around 23 μm. This is related to the fact that the sieve filtration process after the coating is deleted in Comparative Example 4. Phosphors with poor coating effects tend to agglomerate to form larger particles, resulting in larger measured particle size data.

[0106] 3. The phosphors of Examples 1-5 and Comparative Examples 1-4 were immersed in a strong alkaline solution with a pH of 13 for one week, and the appearance was observed and the luminescence performance change data were tested. The results are shown in Table 2.

[0107] Table 2 Appearance and luminescence performance changes of samples after being immersed in a strong alkaline solution with pH = 13 for one week

[0108]

[0109]

[0110] In Table 2, the silicon-phosphorus oxide coated aluminate long afterglow phosphors obtained in Examples 1 to 5 can still maintain more than 80% of the luminous brightness after being soaked in a strong alkaline solution for one week, and the afterglow performance remains basically unchanged. Compared with Example 3, the alkali resistance of Comparative Examples 1 to 4 has decreased to varying degrees. In Comparative Examples 1 and 2, the phosphors obtained by coating only with phosphate or diethyl silicate have a luminous brightness of less than 40% of the initial brightness after being soaked in alkali solution, and the afterglow performance has dropped by nearly or even more than 50%, and agglomeration after hydrolysis has occurred. From the aspects of luminous brightness and afterglow retention rate for 60 minutes, it can be seen that after the ball milling process and the screen filtration process after coating were deleted in Comparative Examples 3 and 4, the alkali resistance of the obtained phosphors has dropped slightly by less than 20%. It can be seen from Comparative Examples 5 and 6 that pH has a great influence on the coating effect of phosphate and the coating effect of tetraethyl orthosilicate. After soaking in a strong alkaline solution, agglomeration and large light decay phenomena similar to those of Comparative Examples 1 and 2 appeared.

[0111] 4. The phosphors of Example 3 and Comparative Example 4 were immersed in a strong alkaline solution of pH for one week, and the alkaline resistance of the phosphors of Example 3 and Comparative Example 4 was tested in parallel. The results are as follows: Figure 2 shown.

[0112] Figure 2 The relative brightness of Example 3 is 85.3% at the minimum and 85.5% at the maximum, with a difference of 0.2% and an average value of nearly 85.4%; the relative brightness of Comparative Example 4 is 74.2% at the minimum and 83.6% at the maximum, with a difference of 9.4% and an average value of nearly 77.8%. The comparison results show that the phosphor of Example 3 obtained by filtering with a mesh after encapsulation has higher performance stability.

[0113] In summary, the present application aims to solve the problem of agglomeration and caking of phosphors in a strong alkaline solution environment by adopting a composite coating of phosphate and silicon oxide, and comprehensively utilizing the close fit between the phosphate film and the phosphor and the compactness of the silicon-phosphorus oxide film, to solve the agglomeration and light decay problems of aluminate long afterglow phosphors, and to improve the luminous efficiency and service life of the phosphors in a strong alkaline solution environment.

[0114] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine different embodiments or examples described in this specification and the features of different embodiments or examples, unless they are contradictory.

[0115] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include at least one of the features. In the description of this application, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0116] The above is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any technician familiar with the technical field can easily think of various changes or substitutions within the technical scope disclosed in the present application, which should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A method for preparing a long afterglow phosphor resistant to high-alkaline solution, characterized in that: The phosphor is an aluminate long afterglow phosphor, and its chemical formula is Sr x Al2O4:Eu 2+ ,Dy 3+ , where 0.6≤x≤1.2; After the phosphor is coated with phosphate, it is further coated with ethyl orthosilicate to obtain the high-strength alkaline solution-resistant long-afterglow phosphor.

2. The method for preparing a long afterglow phosphor resistant to high-alkaline solution according to claim 1, characterized in that: Before phosphate coating, the phosphor is ground into pulp: The powder: water: grinding ball mass ratio is 1: (1.2-1.7): (2.0-2.5), and the mixture is ball-milled for 0.5-1h, and sieved to obtain a phosphor slurry.

3. The method for preparing a long afterglow phosphor resistant to high-alkaline solution according to claim 1, characterized in that: The process of phosphor coating by phosphate is as follows: Add phosphate to the phosphor slurry, adjust the pH to 2-3, and stir at 125-155 rpm for 4-6 hours.

4. The method for preparing a long afterglow phosphor resistant to high-alkaline solution according to claim 3, characterized in that: The phosphate is a soluble phosphate; preferably, the phosphate is disodium hydrogen phosphate and / or sodium dihydrogen phosphate; And / or, the mass of the added phosphate is 10-16% of the mass of the phosphor.

5. The method for preparing a long afterglow phosphor resistant to high-alkaline solution according to claim 1, characterized in that: The process of using ethyl orthosilicate coating is: After the phosphate coating is completed, ethyl orthosilicate is added, and ammonia water is used to adjust the pH to 8.5-10. After the temperature reaction is completed, the reaction is cooled to room temperature to obtain a phosphor slurry coated with silicon-phosphorus oxide.

6. The method for preparing a long afterglow phosphor resistant to high-alkaline solution according to claim 5, characterized in that: After adding ethyl orthosilicate, stir for 1-2 hours, and then use ammonia water to adjust the pH to 8.5-10.

7. The method for preparing a long afterglow phosphor resistant to high-alkaline solution according to claim 5, characterized in that: The conditions for the temperature-raising reaction are: raising the temperature to 70-85° C. and stirring at 180-220 rpm for 2-3 hours.

8. The method for preparing a long afterglow phosphor resistant to high-alkaline solution according to claim 5, characterized in that: After being coated with ethyl orthosilicate, the phosphor powder coated with silicon phosphorus oxide is obtained through separation, washing and drying; that is, the phosphor powder with long afterglow resistance to high-strength alkaline solution.

9. A long afterglow phosphor resistant to high-alkaline solution, characterized in that: The phosphor is prepared by the method for preparing a long afterglow phosphor resistant to high-strength alkaline solution as described in any one of claims 1 to 8.

10. The method for preparing a long afterglow phosphor resistant to high-strength alkaline solution according to claim 9, characterized in that: The phosphor has good fluidity in a pH=13 strong alkaline solution after one week; and / or, a relative brightness of 82.0%-87.1%; And / or, the change in the afterglow maintenance rate for 60 minutes is less than 5%.

Citation Information

Patent Citations

  • Preparation method of acid / alkali-resistant corrosion-resistant aluminum pigment

    CN106700662A

  • A method for obtaining acid- and alkali-resistant blue phosphors by coating 5-sulfosalicylic acid with barium sulfate.

    CN114574191B

  • Method for obtaining acid-resistant and alkali-resistant blue fluorescent powder by coating 5-sulfosalicylic acid with barium sulfate

    CN114574191A

  • High-performance special blue-green fluorescent powder and preparation method thereof

    CN115678541A

  • Film coating method of bismuth vanadate pigment powder

    CN116023801A